Posterior Urethra Rupture: Contrast-Enhanced Computed Tomography Scan and Urethrocystography Demonstrations - Wojciech Marks; S. Dawid; J. Lasek; Z. Witkowski; K. Gołąbek-Dropiewska; M. Stasiak (Case Reports in Urology)
In the follow-up study of patients with pelvic fractures, rupture of the posterior urethra is registered in 3–25% of cases (Koraitim et al., 1996). The diagnostic gold standard for the assessment of hemodynamically stable trauma patients is contrast-enhanced CT scan, especially helical CT. Nevertheless, simultaneous suprapubic cystography and ascending urethrograms (the so-called up-and-downogram) are the investigation of choice in assessing the site, severity, and length of urethral injuries. (Carlin and Resnick, 1995) This paper discusses the evaluation and diagnosis of urethral injury in multiple-trauma patient.